Pemberdayaan UMKM Melalui Pelatihan Pembukuan Dan Pemasaran Digital di Kecamatan Gunung Putri, Bogor - Yulianti Fadilla; Meila Siti Julaeha NB; Virgio Gusdwi Putra; Anisa Cahya Difa; Mohammad Helmi Tsani; Navira Christy Viorenna Pramono; Andi Nugraha; Iis Dewi Herawati; Natalia Titik Wiyani (FKIP, Universitas Palangka Raya, 2025)
Community service activities are carried out in Gunung Putri Village, Gunung Putri District, Bogor Regency. This activity aims to provide support and solutions to the challenges faced by Micro, Small and Medium Enterprises (MSMEs), especially in terms of improving product quality, business management, and market access through training programs, and community counseling. The communities involved can gain new knowledge and skills that can improve the competitiveness of their businesses. These activities include digital marketing training, simple financial bookkeeping, and strengthening local and online marketing networks. In addition, the sustainability of MSME businesses is the main focus, by providing an understanding of the importance of product innovation, knowing the basics and procedures for conducting digital bookkeeping and financial reporting and efficient resource management. The expected result of this community service activity is the creation of MSMEs that are more independent, highly competitive, and able to adapt to technological developments including in terms of financial management. The long-term impact of this program is expected to contribute to the improvement of the local economy in the region.